Integrating Personal Mastery and Team Learning through Strategic Curriculum Design: A Systematic Literature Review - Tegar Adi Satria; Mada Sutapa (LifeSciFi, 2026)
This study aims to systematically examine how curriculum functions as a strategic tool in developing personal mastery and team learning within the context of 21st-century education. The central issue addressed is how effective curriculum design can foster reflective individual growth and support the development of collaborative learning cultures. Qualitative research design using a systematic literature review approach was employed, analyzing articles published between 2018 and 2025 from Google Scholar and Scopus databases. The findings reveal that curriculum designs integrating approaches such as mastery learning, team-based learning, and problem-based learning effectively enhance students’ conceptual understanding, self-directed learning, and collaborative skills. Adaptive and reflective curricula supported by futures literacy and sustainability-oriented frameworks contribute to the development of lifelong learning and organizational learning cultures. The study concludes that curriculum functions as a strategic instrument capable of orchestrating both individual and collective learning processes. It emphasizes the need for flexible, student-centered, and collaborative curriculum models to foster resilient and adaptive educational systems in response to global challenges.